2022
DOI: 10.1007/s12144-022-03069-z
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal relation between time perspective and preventive behaviors during the COVID-19 pandemic: The mediating role of risk perception

Abstract: Understanding psychological factors and the mechanisms involved in compliance with recommended preventive behaviors against COVID-19 is important for effective public health strategies. Time perspective was previously linked with risk perception and health-related behaviors, but it has not been explored in the context of infectious diseases. Furthermore, little is known about the explaining mechanisms that may link time perspective with adoption of preventive behaviors against health threats. The aim of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Studies among the Romanian population also aligned with the results suggested by scholars worldwide, highlighting the negative impact of the COVID-19 pandemic at various levels (Curșeu et al, 2021;Dominte et al, 2022;Măirean et al, 2023;Zancu et al, 2022). For instance, COVID-19 healthcare workers reported high levels of exposure to potentially morally injurious events, which were related to physical and emotional self-reported distress (Maftei & Holman, 2021b).…”
Section: Mental Health Symptomaticallysupporting
confidence: 70%
See 1 more Smart Citation
“…Studies among the Romanian population also aligned with the results suggested by scholars worldwide, highlighting the negative impact of the COVID-19 pandemic at various levels (Curșeu et al, 2021;Dominte et al, 2022;Măirean et al, 2023;Zancu et al, 2022). For instance, COVID-19 healthcare workers reported high levels of exposure to potentially morally injurious events, which were related to physical and emotional self-reported distress (Maftei & Holman, 2021b).…”
Section: Mental Health Symptomaticallysupporting
confidence: 70%
“…Another study conducted in a Romanian sample, mostly comprised of young adults, aimed to identify the relation between time perspective, COVID-19 risk perception and preventive behaviours, over six months. The results showed that participants with a positive orientation toward the future reported more preventive behaviours six months later, while the perceived severity of the COVID-19 pandemic was positively related to preventive behaviours during the second wave (Zancu et al, 2022). The practical implications of these results consist of focusing on the effectiveness of preventive behaviours in protecting against the risks of the pandemic, by highlighting the positive implications of compliance to health protective behaviours.…”
Section: Mental Health Symptomaticallymentioning
confidence: 90%
“… 9 , 32 Zancu et al used Zimbabwe as an example to explore the mediating role of risk perception between time and preventive behavior. 33 Karasneh et al evaluated how the media reshapes the risk perception of pharmacists such that they take more rational preventive actions during a pandemic. 34 In addition to risk perception, trust in the sources of information is a crucial factor that enables the public to take protective actions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Risk perception acts as a mediator in the relationship between the adoption of protective behaviors and temporal perspective (Zancu et al., 2022), which tends to decrease with the progression of the COVID‐19 pandemic (Rattay et al., 2021). Individuals’ risk perception of COVID‐19 has been influenced by the progression of the pandemic (Qiao et al., 2022; Sprengholz et al., 2023).…”
Section: Introductionmentioning
confidence: 99%